2019
DOI: 10.3390/rs11111260
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Remote Sensing-Assisted Forest Inventory: A Glimpse of the State-of-the-Art and Future Prospects

Abstract: Advances in remote inventory and analysis of forest resources during the last decade have reached a level to be now considered as a crucial complement, if not a surrogate, to the long-existing field-based methods. This is mostly reflected in not only the use of multiple-band new active and passive remote sensing data for forest inventory, but also in the methodic and algorithmic developments and/or adoptions that aim at maximizing the predictive or calibration performances, thereby minimizing both random and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Forest inventories based on remote sensing data vary in terms of scale, sensors, and calculated forest structural attributes. For example, Latifi and Heurich [1] reported that lidar point clouds advantageously fused with optical imagery are the most prominent choices for inventory of forest structural variables at the landscape and regional scales. Spatial distribution of trees and standing or fallen dead trees are key forest variables for estimation of forest attributes such as aboveground biomass and growing stock.…”
Section: Introductionmentioning
confidence: 99%
“…Forest inventories based on remote sensing data vary in terms of scale, sensors, and calculated forest structural attributes. For example, Latifi and Heurich [1] reported that lidar point clouds advantageously fused with optical imagery are the most prominent choices for inventory of forest structural variables at the landscape and regional scales. Spatial distribution of trees and standing or fallen dead trees are key forest variables for estimation of forest attributes such as aboveground biomass and growing stock.…”
Section: Introductionmentioning
confidence: 99%
“…Forest inventories based on remote sensing data, particularly lidar point clouds fused with optical imagery, are the most prominent options for the inventory of forest structural variables (Latifi & Heurich, 2019). Forest attributes such as aboveground biomass and growing stock can be estimated from the spatial distribution of tree species and dead wood.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, lidar facilitates precise 3D mapping of forests at the tree level (Reitberger et al, 2008). In combination with MS imagery, lidar has demonstrated promising potential for the calculation of forest structural variables (Latifi and Heurich, 2019).…”
Section: Key Idea and Applicationsmentioning
confidence: 99%
“…Airplanes, helicopters, and innovative platforms such as UAVs equipped with lidar sensors and MS or hyperspectral cameras enable acquisition of high-resolution data from a bird's eye view. In particular, the fusion of lidar point clouds and optical multi-channel imagery is the most prominent option for the inventory of forest structural variables (Latifi and Heurich, 2019). In a preprocessing step, single trees are typically delineated from ALS data.…”
Section: Conventional Approachesmentioning
confidence: 99%
See 1 more Smart Citation